1995
DOI: 10.1002/jcp.1041640109
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the molecular response to DNA damage during cellular aging of cultured fibroblasts: Reduced AP‐1 activation and collagenase gene expression

Abstract: Transcriptional activation of c-fos in response to both serum stimulation and DNA damage requires the serum response element. The inability of in vitro aged or senescent fibroblasts to proliferate in response to serum has been shown to be associated with repressed c-fos expression and reduced AP-1 binding activity. In contrast, we have observed similar levels of c-fos mRNA and protein expression in young (early passage) and old (late passage) cells following their treatment with ultraviolet (UV) irradiation or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…c-fos loses mitogen responsiveness in senescent human fibro blasts [6,[18][19][20]. Thus, c-fos mRNA and pro tein are undetectable in senescent cells, whether or not they are stimulated by serum.…”
Section: Ap-1 Activity Is Lost Upon Cellularmentioning
confidence: 95%
See 1 more Smart Citation
“…c-fos loses mitogen responsiveness in senescent human fibro blasts [6,[18][19][20]. Thus, c-fos mRNA and pro tein are undetectable in senescent cells, whether or not they are stimulated by serum.…”
Section: Ap-1 Activity Is Lost Upon Cellularmentioning
confidence: 95%
“…First, c-fos remains inducible by DNA damaging agents in senescent cells [19]. This suggests that the c-fos damage and mitogen responses are sepa rable, and only the mitogen response is blocked by senescence.…”
Section: Ap-1 Activity Is Lost Upon Cellularmentioning
confidence: 96%
“…A number of studies indicate that AP-1 may be involved in the pathogenesis of hyperoxic inflammatory lung injury. In rats, the level of AP-1 activity is increased in the lung upon exposure to hyperoxia [46,97]. In addition, hyperoxia-induced oncosis of MLE-12 cells is associated with a sustained activation of AP-1 [46].…”
Section: Redox Transcription Factors In Pulmonary Hyperoxic Cell Deathmentioning
confidence: 99%
“…Quantitative and qualitative changes in the synthesis of certain proteins [5][6][7][8] suggest that both efficiency and specificity of the biochemical machinery for protein synthesis may be different in senescent cells. These changes also affect the main components of extracellular matrix (ECM), such as fibronectin [9,10] and collagen [5,11]. We have found that the biosynthesis of proteoglycans (PG) is also modified with senescence [12], since late passage HFs incorporate greater amounts of radioactivity in the large PGs of the cell layer and show a lower ratio between PGs containing dermatan sulphate (DS) and those containing heparan sulphate (HS) [12].…”
Section: Introductionmentioning
confidence: 99%